Obstructive sleep apnea, obesity, and the risk of incident atrial fibrillation - Gami, Apoor S; Hodge, Dave O; Herges, Regina M; Olson, Eric J; Nykodym, Jiri; Kara, Tomas; Somers, Virend K (Journal of the American College of Cardiology, 2007)
This study sought to identify whether obesity and obstructive sleep apnea (OSA) independently predict incident atrial fibrillation/flutter (AF). Obesity is a risk factor for AF, and OSA is highly prevalent in obesity. Obstructive sleep apnea is associated with AF, but it is unknown whether OSA predicts new-onset AF independently of obesity. We conducted a retrospective cohort study of 3,542 Olmsted County adults without past or current AF who were referred for an initial diagnostic polysomnogram from 1987 to 2003. New-onset AF was assessed and confirmed by electrocardiography during a mean follow-up of 4.7 years. Incident AF occurred in 133 subjects (cumulative probability 14%, 95% confidence interval [CI] 9% to 19%). Univariate predictors of AF were age, male gender, hypertension, coronary artery disease, heart failure, smoking, body mass index, OSA (hazard ratio 2.18, 95% CI 1.34 to 3.54) and multiple measures of OSA severity. In subjects <65 years old, independent predictors of incident AF were age, male gender, coronary artery disease, body mass index (per 1 kg/m2, hazard ratio 1.07, 95% CI 1.05 to 1.10), and the decrease in nocturnal oxygen saturation (per 0.5 U log change, hazard ratio 3.29, 95% CI 1.35 to 8.04). Heart failure, but neither obesity nor OSA, predicted incident AF in subjects > or =65 years of age. Obesity and the magnitude of nocturnal oxygen desaturation, which is an important pathophysiological consequence of OSA, are independent risk factors for incident AF in individuals <65 years of age.